2021
DOI: 10.1007/s11119-021-09835-6
|View full text |Cite
|
Sign up to set email alerts
|

Field assessment of a pulse width modulation (PWM) spray system applying different spray volumes: duty cycle and forward speed effects on vines spray coverage

Abstract: The pulse width modulation (PWM) spray system is the most advanced technology to obtain variable rate spray application without varying the operative sprayer parameters (e.g. spray pressure, nozzle size). According to the precision agriculture principles, PWM is the prime technology that allows to spray the required amount where needed without varying the droplet size spectra which benefits both the uniformity of spray quality and the spray drift reduction. However, some concerns related to the effect of on–of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 42 publications
1
37
0
Order By: Relevance
“…In this regard, the authors in [25] identified several concerns related to the effects of on-off solenoid valves and the alternating on-off action of adjacent nozzles on uneven spray coverage, specifically the effects of the PWM duty cycle and sprayer forward speed on the variability of spray coverage under standardized and actual field conditions for an espalier-trained vineyard. They used water-sensitive paper to register coverage variability along the sprayer track, the canopy height and the canopy depth.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the authors in [25] identified several concerns related to the effects of on-off solenoid valves and the alternating on-off action of adjacent nozzles on uneven spray coverage, specifically the effects of the PWM duty cycle and sprayer forward speed on the variability of spray coverage under standardized and actual field conditions for an espalier-trained vineyard. They used water-sensitive paper to register coverage variability along the sprayer track, the canopy height and the canopy depth.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of PPP spray mass balance have reported high spray losses during application [1][2][3][4][5][6][7]. Furthermore, huge variations of spray distribution on the canopies have been observed, because pesticide deposition depends on the vegetation [8][9][10][11][12], equipment [9][10][11][12][13][14], operational parameters [15][16][17][18], weather conditions [19] and spray mix properties [20,21]. PPP losses pose risks both to people (operators, bystanders, residents, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Sprayer adjustment, sometimes referred to as calibration, is aimed at: (i) adjusting the fan airflow rate and its orientation to the tree canopy to minimize off-target losses [35,36,38,39], (ii) balancing the distribution of spray volume between the right and left side of the airblast sprayer [40], (iii) selecting the proper number of active nozzles and setting their orientation to produce a spray vertical profile that matches the targeted canopy as closely as possible [9,36], and (iv) applying the most appropriate spray volume [18,[41][42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, in the field of pesticide application, the correct use of Plant Protection Products (PPPs) is the most common and powerful tool for crop pest control, and, for this reason, it is necessary to satisfy the growing demand for agricultural productivity in a more sustainable way [1][2][3][4][5][6][7][8][9][10]. According to the European Directive 2009/128/EC [11] for spray application, the handling of PPPs is considered an important aspect to avoid undesirable effects on the population and the environment, because, when pesticides are applied to crops, part of the spray may not reach the target, causing serious economic and environmental problems [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%